Different intelligent robust control schemes for precise positioning system - Raafat, Safanah M.; Akmeliawati, Rini; Martono, Wahyudi (2010)
This paper presents the design of two different H∞ robust controllers for a single axis positioning system via two different schemes; The 2 H∞ robust controller, which is suitable for accurate tracking performance and an integrator-H∞ robust controller which can also be tuned for accurate tracking. However, each approach has some certain features that need to be investigated for the application under study. Adaptive neural fuzzy inference system is utilized in both schemes to develop a non-conservative accurate uncertainty weighting function. Both methods can achieve wide bandwidth, high resolution, improved tracking performance, and robustness to modelling uncertainties, as will be demonstrated in the experimental results.